Peruvian patented inventions and their successful commercialization - Rodriguez, Juan Carlos (2014)
Present twelve experiences from peruvian inventors, that from their dreams, motivation, effort and entrepreneurship managed develop innovative products and procedures , with a high degree of commercial success. They patented their invention as a business strategy that has allowed them to get exclusive rights to decide the future of their creations.